SIKAP NASIONALISME DALAM PEMAHAMAN MAKNA SEJARAH PERGERAKAN NASIONAL INDONESIA - Trisnowaty Tuahunse (Jurnal Inovasi, 2008)
Nationalism attitude, understanding the Indonesia national movement, grow through Indonesian struggle to oppose colonialism and imperialism in a great deal to fight and defend Indonesia independence. A Relevance and essential of Indonesia national movement is inspired the nationalism which is need to proses own country. Nationalism is contained basic elements such as the unity and integrity. And the essential of unity or nationalism is not based and group, ethnic, race, language, or religion. Event thought the ethnics, culture and religion are the social factor but by the unity and integrity, realization of nationalism so the society diversity is merged becomes mono socio cultural, it is one nation, on language and one culture of Indonesia. To defend nation exits in this period and future, it is not apart from globalization stress so the unity and integrity were needed or nationalism from all the component of nation in life to mingle the society nation and state. The fieldwork prove that most of the students of UNG Gorontalo still consistent with the unity and integrity or nationalism in socio cultural, socio economic, and socio politic life even trough the changes happened in the social order of society life. However, the nationalism nowadays must be accommodative and adaptive in every aspects of nation, state and society life in other to nation existence can be defended